Adopsi Adaptasi Istilah Ilmu Ekonomi dan Pemerkayaan Kosakata Bahasa Indonesia - Kaharuddin, Kaharuddin (Jurnal Idiomatik Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research aimed to know economics terms which used in everyday while in written media, electronic media, and also in verbal interaction. All of terms be seen if Indonesian vocabularies developed. To catch some information about economics terms, the writer chosed library method with observing and noting the all terms of economics through out of medias (written, electronic) and social interacton. What the writer analized, the writer caught 203 economics terms which used, but only 77 terms or 34.94 percent usually used in communication everyday. It pointed that economics contributed a lot in Indonesian vocabularies developed.